Mechanical properties and failure behavior of resistance spot welded third-generation advanced high strength steels. (May 2021) - Shojaee, M.; Midawi, A.R.H.; Barber, B.; Ghassemi-Armaki, H.; Worswick, M.; Biro, E.
Abstract: Third generation advanced high strength steels are candidates for application in lightweight automotive components due to their remarkable combination of high strength and high ductility. Adoption of these steels is accompanied by challenges to better understand the mechanical performance of their resistance spot welds. In this work, the resistance spot weldability of two third-generation advanced high strength steels, designated herein as 3G-980 and 3G-1180, was investigated. The weldability windows of the steels were developed to determine process robustness and acceptable welding zones for different welding times. The mechanical properties of the spot welds were evaluated by conducting lap-shear and cross tension tests for different nugget sizes. The investigated steels exhibited both interfacial and pullout/partial-pullout failure modes during mechanical testing and the transition points between the failure modes were identified as a function of the welding condition. The optimal weld strengths of the 3G-980 and 3G-1180 samples were 28.7 kN and 30.7 kN for lap-shear and 10.2 kN and 9.4 kN for cross tension specimens respectively. Interestingly, it was shown that even interfacial failure of the joints can demonstrate load-bearing capacities close to the optimized condition in lap-shear testing. Also, in contrast to 3G-980, microhardness measurement of different weldment regions revealed a local drop in the hardness of the sub-critical heat-affected zone for 3G-1180. These measurements were correlated to the crack initiation region and propagation paths of interrupted lap-shear specimens for both steels.